Counter-philology: Ezra Pound as translator of Provencal and Cavalcanti, 1917–1932. Issue 4 (21st April 2019) - McMullan, Luke
ABSTRACT: Pound's Provencal translations 'Homage a la Langue d'Oc' and 'L'Aura Amara' (1918) are characterised by his deployment of philological objects and reading practices against orders of knowledge produced by philological institutions (the 'Germano-American university') in order to see whether and how philology might be poetically 'redeemed'. He used the Scots glossary of a 1710 reprint of Gavin Douglas's Eneados – a Middle Scots translation of the Aeneid – to supply vocabulary for these translations. Read alongside that glossary and 'Provincialism the Enemy' (Pound's 1917 diatribe against philology), Pound's translations were an intervention against the prevailing philological model of knowledge he and others identified with the nationalism and racism of the Second German Empire. However, his work on Cavalcanti in the late 1920s, some of which appeared in Guido Cavalcanti Rime (1932), arguably adopted the philological tendencies excoriated in 'Provincialism'. Amid current interest in philology as a historical discipline, these poems offer an example of negotiations between poetry and philology. The concept of philological poetry offers an account of such negotiations across periods amid pedagogical institutional contexts.